HUBUNGAN PENGETAHUAN DAN SIKAP SANTRI TERHADAP KEJADIAN SKABIES DI PONDOK PESANTREN DAREL HIKMAH KOTA PEKANBARU TAHUN 2014 - Febrianti Febrianti; Rika Sri Wahyuni (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Scabies is a skin disease caused by mites Sarcoptesscabiei var. Horminis make tunnels in the stratum corneum of the skin that is easily transmitted from animals to humans. According to the Ministry of Health of the Republic of Indonesia (RI) prevalence of scabies ranks of three of the most common skin disease 12. The cause was staying with a group of people who are at risk of contracting various diseases especially easy skin diseases. Based on the research results Yuzzi Afraniza in 2011 at Demak boarding school of 66 students found that 30 students (45,5%) were suffering from scabies and research results Frenki boarding school in 2011 in the city of Pekanbaru Darel Hikmah of 72 students there are 36 cases (50%) suffering from scabies. The purpose of this study was to determine the relationship of knowledge and attitudes of students toward the incidence of scabies in boarding school DarelHikmahPekanbaru city in 2014. Quantitative research with the type of research design and analytic cross-sectional approach. This study uses primary data to the entire population that boarding school students Darel Hikmah Pekanbaru city in 1446 a number of students and the sample was 94 students. This study used a questionnaire instrument and data retrieval technique with stratified propottional random sampling , processing, univariate and bivariate data. Results reveal that the majority of students have low knowledge of as many as 48 students (51,1%), have the negative attitude many as 49 students (52,1%), and those with scabies as many as 48 students (51,1%). From the results obtained chi-square test p value > 0,1 means there is no correlation between knowledge of students on the incidence of scabies, and p value < 0,1 means there is a correlation between knowledge of students on the incidence of scabies. From the results of this study hopes to become an input for further research and institutional Midwifery Academy International.